Deplorable Living Conditions of Female Workers: A Study in a Tea Garden of Bangladesh - Hassan, A.B.M Enamol (American Journal of Humanities and Social Sciences, 2014)
The study reveals the living conditions of the female laborers of tea garden in Bangladesh exploring the social and job environment with the inclusion of consciousness level as the deplorable scenario of their life styles. This research has been done in a tea garden of Sylhet district in Bangladesh namely Lackatoorah Tea Estate, as the study area, taken into account at random. It shows that female workers are being oppressed and suppressed in each and every sphere of life as from family residence to job field. It also exhibits very explicitly that 68 percent of female workers have no control over their own income. 94 percent have no hereditary property ownership though they are entitled to get it legally from their family. 92 percent females think that they are being physically tortured and mentally harassed by their husband, male members of family and also by representative of estates manager. 86 percent women want to keep small size of family but cannot play role in the decision making of child issue. The study is fully based on primary level data that followed stratified sampling method with triangulation research design and reviewing some related literatures from past research reports.